Pengaruh Fluktuasi Harga Minyak pada Ekspor Minyak Mentah Negara-Negara Wilayah OPEC (Periode 1970 – 2005) - Abdul Aziz Ahmad (EKO-REGIONAL, 2007)
This research pressures to export demand of opec crude oil. It concern primarily on the impact of price oil shock toward OPEC crude oil export. Ordinary Least Square (OLS) is not proven accurately to analyze volatile phenomenon of OPEC export demand of crude oil. Otherwise, General Autoregressive Conditional Heteroskedastic (GARH) and specifically Exponential GARCH give practical and logical model to be applied. It shows that structural break occur in price oil variable and then impact to volatile of crude oil export. Several important world events create structural break and this “bad news” has significant impact to instability of oil price. This result gives also that nominal crude oil price adjusted for exchange rates and demand export of Non-OPEC crude oil have negative impact, and OPEC proven crude oil reserve and Exports of refined products by OPEC have positive impact to OPEC crude oil export. Keywords: crude oil price, structural break, export demand, GARCH and EGARCH,